Language, Authority, and Identity: Shia-Salafi Debates on Imamate and Nationalism in Indonesia’s Online Sphere - Faizin, Khoirul; Hepni, Hepni; Basyir, Kunawi; Fauzi, Ahmad (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2025)
This study stems from a gap in research on how the concepts of Imamate and nationalism are contested within Shia-Salafi dynamics in Indonesia’s digital space. Most previous studies have emphasized aspects of social conflict, whereas the linguistic mechanisms that shape religious-political authority remain underexplored. This study argues that the contestation of religious legitimacy should be examined through patterns of discourse production that link doctrinal teachings, group identities, and the constructions of nationalism they articulate. The research analysis on 50 articles from Safinah.id and Annasindonesia.com to identify how each site constructs its ideological position through the linguistic practices it deploys. The study employs Norman Fairclough’s critical discourse analysis, which encompasses the dimensions of text, discursive practice, and social practice in an integrated manner. The findings show that identity, claims of authority, and symbolic boundaries are constructed through linguistic strategies that systematically produce oppositions and assert hierarchies of truth. This research contributes theoretically by linking its findings on the construction of Shia-Salafi authority in the digital space with Campbell and Bunt’s conceptual framework on the formation of identity, authority, and religious practices in the online ecosystem. The implications of this research open pathways for further studies on the dynamics of religious power operating through linguistic practices in Indonesia’s digital media landscape.